1989
DOI: 10.1083/jcb.108.4.1537
|View full text |Cite
|
Sign up to set email alerts
|

Localization of transferrin receptors and insulin-like growth factor II receptors in vesicles from 3T3-L1 adipocytes that contain intracellular glucose transporters.

Abstract: Abstract. Transferrin receptors in detergent extracts of subcellular membrane fractions prepared from 3T3-L1 adipocytes were measured by a binding assay. There was a small but significant increase (1.2-fold) in the amount of receptor in a crude plasma membrane fraction and a 40% decrease in the number of transferrin receptors in microsomal membranes prepared from insulin-treated cells, when compared with corresponding fractions from control cells. Intracellular vesicles containing insulin-responsive glucose tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
64
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 42 publications
10
64
0
1
Order By: Relevance
“…Moreover, Tanner and Lienhard [7] showed that, at least in adipocytes, GLUT1, TfR and M6PR are colocalized in an intracellular vesicle population. It is now well established that these membrane proteins recycle between an intracellular pool and the plasma membrane, and that this recycling involves the endosomal system (for a review, see [9]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Tanner and Lienhard [7] showed that, at least in adipocytes, GLUT1, TfR and M6PR are colocalized in an intracellular vesicle population. It is now well established that these membrane proteins recycle between an intracellular pool and the plasma membrane, and that this recycling involves the endosomal system (for a review, see [9]).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous endosomal membrane proteins, including the mannose-6-phosphate receptor (M6PR) [5], the transferrin receptor (TfR) [6,7], GLUT1 [8] and the α2-macroglobulin receptor also translocate to the plasma membrane upon insulin stimulation in adipocytes. Moreover, Tanner and Lienhard [7] showed that, at least in adipocytes, GLUT1, TfR and M6PR are colocalized in an intracellular vesicle population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin influences the iron uptake and storage by increasing the cell surface transferrin receptors (1), reciprocally iron influences the insulin activity by interfering with glucose uptake and utilization (2). Iron causes hyperinsulinaemia by decreasing the insulin uptake and metabolism by hepatocytes (3).…”
Section: Introductionmentioning
confidence: 99%
“…This observation may signify that these proteins are colocalized in a single intracellular pool enabling them to be recruited to the PM simultaneously upon insulin stimulation. Such a proposition is not without precedent given that other proteins, such as the transferrin receptor and the mannose 6-phosphate receptor, whose cellular distribution is also affected by insulin, have been colocalized with intracellular GLUT4 in 3T3-L1 adipocytes [13]. In an attempt to address this question and gain further insights into the nature of the intracellular pools containing the insulin-senstive GLUT4 transporter and the subunits of the Na,K-ATPase we have, in this investigation, studied the sedimentation and immunological characteristics of intracellular membranes containing these proteins.…”
mentioning
confidence: 99%